Management of tibial diaphyseal fractures with linear external skeletal fixators using carbon connecting rods in dogs - PHANEENDRA, M S S V; LAKSHMI, N DHANA; PRASAD, V DEVI; RAJU, N K B (The Indian Journal of Animal Sciences, 2016)
Dogs (12) with unstable tibial diaphyseal fractures, selected for this study, were stabilized with bilateral uniplanar Type II external skeletal fixators using stainless steel positive profile centrally threaded transfixation full pins, 2- way AO clamps and indigenously designed carbon fiber rods. Clinical lameness evaluation and radiographic evaluation for fixator stability, fragment alignment and callus formation were studied. Post-operatively, no breakage or bending of the carbon fiber rods was seen throughout the fixation period. Fixator staged disassembly and complete removal was done on an average 4–9 weeks in all cases which showed grade I lameness after removal. Complications like pin tract infection, wound at suture site due to wound dehiscence and wound at pin-skin interface were seen, which subsided later without any affect on bone healing. Lameness grading, pain score and radiographic evaluation of healing were estimated in all the cases throughout the fixation period. ESF using carbon fiber connecting rod appears as a practicable method for repair of tibial diaphyseal fractures with minimum risk of fixator destabilization. Fixator staged disassembly at 4 weeks accelerated bone healing and promoted earlier limb function.